Gene by environment interaction effects on the metabolic subtype of Polycystic Ovary Syndrome in Hispanic Community Health Study/Study of Latinos - Hridya R. Gardner; Michelle L. Meyer; Jennifer K. Wagner; Krista M. Perreira; Laura Y. Zhou; Martha Daviglus; Christina Cordero; Anne E. Justice; Lindsay Fernandez-Rhodes (Frontiers in Genetics, 2026)
Polycystic Ovary Syndrome (PCOS) is a common polygenic endocrine disorder that is heterogenous in clinical presentation across genetic ancestry groups. PCOS is characterized by an array of symptoms such as hyperandrogenism, impaired mental health, and metabolic dysregulation. Studying the interaction of environmental factors (such as diet, physical activity, anxiety, and depression) with genetic variants on PCOS and its subtypes in populations with high cardiometabolic burden, e.g., Hispanic/Latinas, could aid in unraveling pathophysiological and genetic pathways through which PCOS functions. We sought to study gene by environment interactions with PCOS and its metabolic subtype (mPCOS) in a sample of US Hispanic/Latina female adults from the Hispanic Community Heath Study/Study of Latinos. In this large community-based study, we derived PCOS using self-reported condition and menstrual cycle information. We classified females with PCOS as having mPCOS if they had high metabolic impairment (fasting glucose, fasting insulin, or body mass index higher than the 75th percentile). There were 451 individuals with PCOS and 221 of them had mPCOS in our sample. We found that PCOS and mPCOS were significantly associated with hyperglycemia and high triglycerides in this population. While a polygenic risk score derived in European ancestry did not generalize to Hispanic/Latina females with PCOS, we identified the best proxy genetic variants in this population in known PCOS regions and investigated their interactions with four environment variables (diet, physical activity, anxiety and depression). Associations with known PCOS loci were generalized in our study at STAG3L4 and CACNA1G genomic regions. We observed GxE interactions between variants in/near three genes and physical activity on PCOS and mPCOS, including FGGY , FAT1 , and PTHLH . Additionally, we noted interactions between diet and a variant in FANCC on PCOS, and diet and a variant near CMAS on both PCOS and mPCOS. We also detected GxE interactions between anxiety and depression and a variant in FGGY on PCOS, and depression and a variant near FBP1 on mPCOS. Our results point to potential protective effects of physical activity in females with PCOS and could inform future research on the mitigating effects of lifestyle management on PCOS genetic risk in Hispanic/Latino populations.